Impacts of policy reforms on forestry environments and biodiversity - Sayer, Jeffrey A.; Changjin Sun (Resources for the Future and Center for International Forestry Research, 2003)
China has serious environmental problems but China has begun to address some of them. The data for environmental assesments of China's forests are sparse at best, therefore, the authors survey general impressions before focusing on one representative topic, the loss of biodiveristy that necessarily occurs as China deplete its natural forests. China's large expanse of natural forest may support the largest range of biodiversity as well. Managed forests support some environmental services and they play a crucial role in controlling erosion, but they are not as important as natural forests for the protection of critical habitats and general biodiversity. The central government has identified the enviroment as a focal policy issue for the twenty-first century, and it has begun enforcing compliance with environmental regulations on polluting industries. It is insufficient to presume that comprehensive rules such as increasing forest cover in general, or even saving all natural forests, will solve all forestry problems. Beter data and more thorough analyses are needed to assess the relative magnitudes of these problems and the most effective means of addressing them.